The modal future a theory of future-directed thought and talk - Cariani, Fabrizio (Cambridge University Press, 2021)
"The author's overarching theme of the book is the thesis that thought and talk about the future is modal. The linguistic aspect of this thesis is that the meanings and contents of future-directed claims, like the water will boil are best understood in terms of a fundamental parallel with counterfactual claims, like the water would have boiled if you had turned on the stove managed to get valuable feedback at a virtual philosophy of an guage work-in-progress group, "--